Quest for Industrialization in Nigeria: The Role of the Development Bank of Nigeria - Ogbuabor, Jonathan E.; Orji, Anthony; Anumudu, Charles N.; Onwumere, Josaphat U.; Manasseh, Charles O. (International Journal of Economics and Financial Issues, 2018)
The benefits of industrialization in employment generation, poverty reduction, improved living standard, improved economic growth and development, balance of payment stability, self-reliance, stimulation of other sectors of the economy, and development of skilled manpower have been well established in the literature. However, access to finance for industrial development has remained a key challenge in Nigeria. In view of this, this paper describes what the structure and operations of the Development Bank of Nigeria (DBN) should be so that the Bank will not only deliver on the core mandate of empowering MSMEs but also support the nation’s quest for industrialization by adequately funding national priority projects in the areas of infrastructure, basic industries, energy, transportation, and the likes. The paper argues that limiting the mandate of the DBN only to facilitating credits for MSMEs in the informal sector will not go far in advancing Nigeria’s quest for industrialization. Keywords: Industrialization; Development Banking; Economic Development; Nigeria JEL Classifications: O14; E51; O23; N17